REFORMASI PARADIGMA DAN TRANSPARANSI KEUANGAN PEMERINTAH DAERAH - Drs. H. Awang Faroek Ishak (Jurnal Borneo Administrator, 2005)
During New Order epoch, Indonesia’s governmental system was very centralized. Consequently, local governments’ dependency on central government budget and policies is remarkably apparent. The genesis of 1999 extended-decentralization framework aims not only to reduce the fiscal dependency, but also to alter the development paradigm from growth-oriented to distribution and equity-oriented strategies. In other words, the purpose of regional autonomy is actually to strengthen the economic basis of local development. In order to attain such idea, this paper highlights the importance to reform the existing budgeting system and cycles.